ANALYSIS CONSUMER PREFERENCES FOR BRAND IMAGE OF FOREIGN AND DOMESTIC DAIRY PRODUCTS IN MANADO - Liow, Christiani; Mekel, Peggy A.; Tielung, Maria V. J. (FEB Universitas Sam Ratulangi Manado, 2014)
All of the consumers that used foreign product and domestic product have their own perception why they used foreign product and why they used domestic product. Phenomenon in dairy consumption in Manado is not so much different from other big cities in Indonesia. Most of the people have a tendency to consume foreign dairy dairy products thanthedomestic one. In fact, still there are a few consumers who prefer to consume domestic products rather than foreign product. However, this situation is unclear about the reason consumers of dairy products in Manado to choose foreign product or select domestic product. The purpose of this research is to analyze the consumer preferences of foreign and domestic dairy products in Manado. This research used qualitative approach and descriptive method. The data is collected through the interview as case study types. The analysis is descriptive process, and there are 15 informants as research samples. The result of this research show that most of the informants prefers for foreign dairy product rather than domestic dairy product. There are five indicators of consumer preferences, which are: product quality, reference group, brand loyalty, price, and packaging. This research suggest the company that produce domestic dairy product to improve their marketing ways and find solutions to promote their product and for the company that produce foreign dairy product to make another product innovation to attract the consumers to keep buying their products. Keywords: consumer preferences, brand image, product